Leg Muscle Explosive Power, Foot Coordination and Concentration Can Influence The Accuracy of Goal Shooting - Mohendra, Yogi; Sin, Tjung Hauw; Arsil, Arsil; Rasyid, willadi; Andika, Heru (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
By carrying out this research, the aim is to analyze the direct influence of Leg Muscle Explosive Power, Simultaneous Ankle Coordination on Shooting Accuracy through Concentration in SMKN 3 Sungai Full football players. The method used in this research was a quantitative method with 24 participants. The data analysis technique uses a path analysis approach using SPSS version 26. Based on the results of research that has been carried out, it can be stated that muscle explosive power has a contribution of 13.1%, and eye-foot coordination has a contribution of 12.8%, while concentration has a contribution amounting to 13.6%. So it can be conveyed that shooting accuracy can be influenced by explosive power, muscle coordination, eye-foot coordination and concentration, this needs to be understood and studied at an advanced level for shooting accuracy.